Analysis of the current status and influencing factors of nurses’ patient safety competence: a potential profile analysis - Xiao, Qian; Huang, Xi; Ren, Xin; Wen, Xiulin; Zhao, Yujian (Frontiers in Medicine, 2024)
Objective The study aimed to understand the current situation of hospital nurses’ patient safety competence, identify potential categories, and analyze the distribution characteristics of demographic variables in each subgroup. Methods A total of 1,996 nursing staff were selected to be included in this research using a convenience sampling method. A questionnaire survey was conducted using the Chinese version of the Patient Safety Ability Scale, and three dimensions of the Patient Safety Ability Rating Scale were used as explicit variables for potential profile analysis. The influencing factors of different potential profiles of nurses’ patient safety ability were analyzed using logistic regression analysis. Results The safety ability of the 1,996 nurses could be categorized into three potential groups as follows: “ability risk group” (14.3%), “medium ability group” (32.9%), and “ability advantage group” (52.7%), with monthly income, participation in department training, self-learning, and love of nursing as the influencing factors. Conclusion The overall patient safety ability of nurses is at an upper-middle level. The classification of nurses can be predicted by factors, such as monthly income, participation in department training, self-directed learning, and love of nursing. Nursing managers can formulate targeted interventions according to the influencing factors of potential profiles to improve nurses’ patient safety ability.